2019
DOI: 10.1002/lary.28202
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced epithelial sinonasal tumors: The impact of multimodal approach

Abstract: Objective Outcomes of locally advanced epithelial sinonasal cancers remain unsatisfactory; moreover, only limited and heterogeneous data exist on prognostic factors. Methods We reviewed all consecutive patients with American Joint Committee Cancer stage III to IV epithelial sinonasal cancers treated with platinum‐based induction chemotherapy (IC) followed by locoregional treatment between 1996 and 2015. Results We identified 69 patients treated with a multimodal approach (IC, surgery, radiotherapy). Overall, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…Additionally, we observed that for SNM patients treated with SS, SCC histology had a poor long‐term OS outcome, representing a highly aggressive neoplasm. Locally advanced SNM treated with a multimodal approach has a high propensity for recurrence, with SS providing an opportunity for longer OS 20 . However, as suggested by our current study results, PS may be the best option for improved OS outcomes over SS, whenever surgical resection is an option.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Additionally, we observed that for SNM patients treated with SS, SCC histology had a poor long‐term OS outcome, representing a highly aggressive neoplasm. Locally advanced SNM treated with a multimodal approach has a high propensity for recurrence, with SS providing an opportunity for longer OS 20 . However, as suggested by our current study results, PS may be the best option for improved OS outcomes over SS, whenever surgical resection is an option.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, in the setting of residual disease, salvage surgery would be indicated for definitive treatment 2,5,10,11,19 . Although the OS benefit of salvage surgery has been documented for patients with advanced SNM experiencing recurrence following upfront surgical or nonsurgical therapy, 10,11,16,20 there are limited data comparing the OS of different surgical sequences for SNM. Therefore, this study used a large‐population national database to compare the clinical outcomes of primary surgery (PS), followed by adjuvant nonsurgical therapy versus upfront nonsurgical therapy, followed by salvage surgery (SS) for SNM based upon stage, histology, and primary site.…”
Section: Introductionmentioning
confidence: 99%
“…Tumours affecting patients included in the analysis are heterogeneous, so the therapeutic alternatives varied, being cancer-specific: patients with ACC often undergo a watchful waiting approach or receive systemic chemotherapy, even with disappointing results, only in case of rapidly progressing disease 23 ; patients with SDC can be treated with androgen deprivation therapy 24 or with chemotherapy 25 ; patients with MTC benefit from tyrosine kinase inhibitors, especially when bearing RET alterations 26 ; radioactive iodine-refractory DTC can be effectively treated with antiangiogenic lenvatinib 27 ; retrospective case series of TACE in both MTC 28 and DTC 29 have been published; recurrent/metastatic NPC responds to platinum-based palliative chemotherapy 30 ; and metastatic sinonasal cancer has a dismal prognosis, especially when not responding to systemic therapies. 31 In this case series, the choice of treating patients with extrahepatic metastases with liver-directed therapy was made when liver disease was the only predominant progressing site. In case of concurrent pretreatment hepatic and extrahepatic progression, the decision to deliver a local liver approach was deemed to have an impact on patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with sinonasal carcinomas, despite progress in therapy modalities and regimes, remains poor. Tumor histology, T and N stage, and age are factors that influence therapy outcome [ 5 , 6 ]. Five-year overall survival ranges from 30–80% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five-year overall survival ranges from 30–80% [ 2 ]. The median OS time is given with 27.6–98.6 months [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%